Answers

The Brainliest Answer!
2014-07-17T21:02:17+05:30
See this can be done as
  S=1*2 + 2*2^2 + 3*2^3...........100*2^100
2S=         1*2^2 + 2*2^3...........  99*2^100 + 100*2^101
-              -        -                       -             -
-------------------------------------------------------------------------------------------------
-S=2 + 2^2 + 2^3 +............2^100 -100*2^101
using sum of gp formula we will get
-S=2(2^100-1) -100* 2^101 
S=100*2^101 - 2^101 - 2
S=2^101(99) - 2

2 5 2
but you done a very small mistake at last s=2^101(99)+2
oh sorry